REVOLUSI MEDIA, JURNALISME GLOBAL, DAN HUKUM PERS INDONESIA - Wardaya, Manunggal K.; Komari, Ahmad (Faculty of Law, Universitas Jenderal Soedirman, 2011)
The development in information technology influences many aspects of human life including news media. Various definitions in media have encountered significant changes and cannot anymore be us-ed. Press Law as a main regulation of news media Indonesia is no exception. Its relevancy is now be-ing questioned and even challenged when it fails to adopt with the changes in society. This article believes that the amendment of Press Law should be done so that it will be responsive towards the need of the constantly-changing society. Keywords: information technology, media, press, citizen journalism